Distribution of major diazotrophs in the surface water of the Kuroshio from northeastern Taiwan to south of mainland Japan. (11th July 2018) - Shiozaki, Takuhei; Kondo, Yoshiko; Yuasa, Daisuke; Takeda, Shigenobu
Abstract: We investigated the composition and distribution of diazotrophs in waters of the Kuroshio, the "hot spot" of nitrogen fixation in the Pacific Ocean, as well as in adjacent waters and the North Pacific tropical gyre (NPTG). Specifically, we explored the abundance of nifH in seven commonly observed diazotrophs: Trichodesmium, Crocosphaera, UCYN-A, UCYN-C, Richelia associated with Rhizosolenia (RR) or Hemiaulus (HR) and a gammaproteobacterium (γ-24774A11). The surface diazotroph community in the Kuroshio was distinguished from those in other waters by its higher abundances of Trichodesmium, RR, HR and UCYN-C. The distributions of these diazotrophs were not well explained by temperature and macronutrient concentrations, although they may be influenced by the current flow and micronutrient content. γ-24774A11 occurred extensively in the oligotrophic waters, and its abundance was significantly correlated with water temperature. The surface abundances of Crocosphaera and UCYN-A1 decreased from upstream to downstream in the Kuroshio, and their abundances were lower in the Kuroshio than in the NPTG. Temperature and nitrate + nitrite levels were comparable between the Kuroshio and NPTG, but phosphate and chlorophyll a level were lower and higher, respectively, in the Kuroshio. These results suggest that the growth of Crocosphaera and UCYN-A1 in the Kuroshio may be regulated by phosphorus availability, which would be severely limited due to intense competition with non-diazotrophs and other diazotrophs.